Level of knowledge and workload are associated with nurse’s adherence in implementing fall prevention procedures at Tabanan District Hospital, Bali - Sulawa, I Ketut; Wirawan, Made Ady; Putri, Wayan Citra Wulan Sucipta (Universitas Udayana, 2021)
Background and purpose:Fall prevention is an essential part of patient safety system. At Tabanan District Hospital (BRSUD Tabanan), incidence of falling among patients is still happening. This study aims to determine the relationship between level of knowledge and workload of nurses with compliance in implementing standard operational procedures (SOP) to prevent the risk of falling in the inpatient rooms at Tabanan District Hospital. Methods: This study was a cross-sectional survey. The sample size was 75 nurses in the inpatient room at BRSUD Tabanan. Data collection was carried out in the period of December 2, 2019 - January 2, 2020 which included 1). direct interviews to obtain data on characteristics, the level of knowledge and workload of nurses, 2). observations of nurses’ adherence in the implementation of standard operational procedures to prevent the risk of falling patients. Data analysis was performed by univariate, bivariate with chi-square test and multivariate analysis with logistic regression. Results: Most of the respondents were ≤40 years old (86.7%), female (72%), length of working ≤10 years (81.4%), education level of bachelor in nursing (65.4%). Two third of the respondents have a good level of knowledge (66.7%), with medium workload (26.7%) and heavy workload (73.3%). Most of the respondents (70.7%) adhere to the implementation of standard operating procedures to prevent the risk of falling patients. Variables associated with the compliance to SOP are age (AOR=5.35; 95%CI: 1.230-23.259; p=0.025), level of knowledge (AOR=6.409; 95%CI: 1.720-23.873; p=0.006), and workload (AOR=0.076; 95%CI: 0.17-0.339; p=0.001), where the workload variable has a negative relationship with nurse compliance (AOR<1). Conclusion: The conclusion of this study is that there is a relationship between the level of knowledge and workload on nurses’ compliance in implementing standard operational procedures to prevent the risk of falling patients